Legal Analysis of in-house home credit schemes reviewed from the Perspective of Contract Law - Suryaningsih, Suryaningsih; Zainuri, Zainuri; Shofiatul Azmi (International Journal of Technology and Education Research, 2024)
Home is a very crucial thing in human life. The growth and development of each individual and how they are formed at home determines their future lifestyle. As we know, the payment methods that have been applied to most developers are cash, in-house, and mortgage payments. The research method used by the author is the doctrinal legal research method or normative law, namely research that uses legislation, legal rules, and norms as sources of law related to the problems to be studied. The purchase agreement in the Civil Code is regulated in Book III on obligations (Van Verbintenissen) Chapter 5, so that buying and selling is an agreement. The legal analysis of in-house home credit schemes from the perspective of contract law reveals several key insights regarding their structure, risks, and the protection of parties involved. Continued legal oversight and potential reforms may further enhance the efficacy and integrity of these credit schemes in the real estate market.